Swaddle bathing in premature babies in a neonatal unit: the practice from the perspective of nurses - Hisabela Marinheiro dos Santos; Laura Johanson da Silva; Fernanda Garcia Bezerra Góes; Ana Carolina Nascimento dos Santos; Bárbara Bertolossi Marta de Araújo; Inês Maria Meneses dos Santos (Universidade Federal do Ceará, 2020)
Objective: to understand the practice of swaddle bathing in premature babies, in a neonatal unit, from the perspective of nurses. Methods: qualitative research, conducted through semi-structured interview, with 13 nurses working in neonatal units, captured through the snowball sampling technique. Data submitted to thematic-categorical analysis. Results: nurses considered benefits related to comfort and stimulation in the swaddle bathing. However, they mentioned challenges for practice, related to lack of knowledge, low adherence and work overload of the nursing team, absence of routines and institutional protocols, besides to scarcity or even inadequacy of the material resources available in the institutions. Conclusion: the practice of swaddle bathing, from the perspective of nurses, has positive effects for the premature babies' development. Nevertheless, there are managerial challenges that need to be overcome for effective implementation.